2017
DOI: 10.3390/rs9121296
|View full text |Cite
|
Sign up to set email alerts
|

An Incomplete Inventory of Suspected Human-Induced Surface Deformation in North America Detected by Satellite Interferometric Synthetic-Aperture Radar

Abstract: Abstract:We used satellite interferometric synthetic-aperture radar (InSAR) data to document ground deformation across North America suspected to be caused by human activities. We showed that anthropogenic deformation can be measured from space across the continent and thus satellite observations should be collected routinely to characterize this deformation. We included results from the literature as well as new analysis of more than 5000 interferograms from the European Remote Sensing (ERS) satellite, Envisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 55 publications
0
9
0
1
Order By: Relevance
“…These surface deformation measurements can be used to derive information about Earth's subsurface, estimate the distribution of fault slip, and infer associated seismic risk (Elliott et al, 2016; Huang et al, 2017; Segall, 2010). Within Texas, Shirzaei et al (2016) reported indications of surface uplift due to wastewater injection near a 2012 M 4.8 earthquake, though limited validation for the ALOS data was available at this site near Timpson, TX (Semple et al, 2017). Kim and Lu (2018) detected multiple deformation bowls within the Delaware Basin related to wastewater injection, CO 2 injection, and hydrocarbon production using Sentinel‐1 InSAR data.…”
Section: Introductionmentioning
confidence: 99%
“…These surface deformation measurements can be used to derive information about Earth's subsurface, estimate the distribution of fault slip, and infer associated seismic risk (Elliott et al, 2016; Huang et al, 2017; Segall, 2010). Within Texas, Shirzaei et al (2016) reported indications of surface uplift due to wastewater injection near a 2012 M 4.8 earthquake, though limited validation for the ALOS data was available at this site near Timpson, TX (Semple et al, 2017). Kim and Lu (2018) detected multiple deformation bowls within the Delaware Basin related to wastewater injection, CO 2 injection, and hydrocarbon production using Sentinel‐1 InSAR data.…”
Section: Introductionmentioning
confidence: 99%
“…The literature illustrates various examples of geohazards triggered by the hydrocarbon industry around the globe such as ground displacements associated with fluid injection and extraction [1][2][3] ; seismicity induced by fluid extraction and associated surface deformation (e.g. Lacq gas field in France 4 , the Groningen field in the Netherlands 5 ); seismicity correlated to the injection of wastewater and enhanced oil recovery 6 , to shale gas hydraulic fracturing [7][8][9] , and to hydraulic stimulation for enhanced geothermal systems, which operates in a similar way to hydrocarbon production 10 .…”
mentioning
confidence: 99%
“…As SAR satellite sensors have a side-looking view, PSI displacements can be measured only along the LOS direction, which in the study area is in the range of 22-34 • (Table 1). Observed increases or decreases in the LOS can be due to ground subsidence and uplift, respectively, although horizontal motions do occur and can dominate in some locations [24]. For those areas common to both acquisition geometries, the overlapping availability of ascending and descending PSI datasets allows for the evaluation of two spatial components (vertical and E-W horizontal ones) of ground deformation, based on simple trigonometric rules [5,14], as the N-S horizontal component is not detected by the SAR satellite acquisition system.…”
Section: Psi Datasets Post-processing For Ground Deformation Componentsmentioning
confidence: 99%